Differences of Dyspareunia in Primipara with 2nd Degree Perineal Laceration Sutured with Rapide Polyglactin 910 and Chromic Catgut Threads - Satrio Arief Wibowo; Yuli Trisetiyono; Herman Kristanto; Putri Sekar Wiyati; Hary Tjahjanto; Erwinanto Erwinanto (Medica Hospitalia : Journal of Clinical Medicine, 2024)
BACKGROUND: Dyspareunia is persistent or recurrent pain during sexual intercourse. Perineal laceration, spontaneous or episiotomy, is one of the most common causes. Perineal lacerations that occur must be treated through suturing. Chromic catgut is a natural thread that is often used in medical practice, but this thread have a higher inflammatory response compared to Rapide Polyglactin 910. AIMS: To analyze the difference in the incidence of dyspareunia in primipara with 2nd degree perineal lacerations sutured with Rapide Polyglactin 910 and Chromic catgut threads METHOD: True experimental research with randomized controlled trial-single blinded method. The research was conducted at dr. Kariadi Semarang, RA Kartini Hospital and dr. Soeselo from August 2022 to February 2023. The research subjects were primipara with 2nd degree perineal lacerations which were divided into 2 groups, namely 45 subjects in the Chromic catgut group and 45 subjects in the Rapide Polyglactin 910 group. Evaluation of dyspareunia after 3 months was carried out using the Female Sexual Function Index (FSFI) RESULT:  Subjects sutured using Chromic catgut had a 2.7 times greater risk of experiencing dyspareunia when compared to using Rapide Polyglactin 910 (OR=2.7; 95% CI=1.1-6.6). A significant confounding factor was found, namely the act of episiotomy (p=0.047; OR=9.56; 95% CI=1.86 - 48.97). After controlling for these variables, the subjects who were sewn using Chromic had a significant risk (p=0.002, OR=5.39; 95% CI=1.76-16.50) CONCLUSION: Subjects with Chromic catgut have a higher risk of experiencing dyspareunia than using Rapide Polyglactin 910 threads after 3 months of suturing.